2014
DOI: 10.1007/s12160-014-9592-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Feasibility of a Tele-health Intervention for Acute Coronary Syndrome Patients with Depression: Results of the “MoodCare” Randomized Controlled Trial

Abstract: ACTRN1260900038623.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
39
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 32 publications
(34 reference statements)
2
39
0
2
Order By: Relevance
“…Although more intensive treatments often produce gains twice as large as collaborative care interventions (effect size: 0.6 vs. 0.3) (10), they can be difficult to provide at scale or to patients who have difficulty taking time off from work, live in rural areas, or have other transportation issues (11). Consequently, the report by O’Neil and colleagues (12) describing the efficacy and feasibility of a telehealth intervention for depressed ACS patients in this issue of the Annals is timely.…”
mentioning
confidence: 99%
“…Although more intensive treatments often produce gains twice as large as collaborative care interventions (effect size: 0.6 vs. 0.3) (10), they can be difficult to provide at scale or to patients who have difficulty taking time off from work, live in rural areas, or have other transportation issues (11). Consequently, the report by O’Neil and colleagues (12) describing the efficacy and feasibility of a telehealth intervention for depressed ACS patients in this issue of the Annals is timely.…”
mentioning
confidence: 99%
“…35,37,38 These results mirror trial outcomes in other types of e-health treatments. 19,3942 In several studies included in this review, however, the issue of programme adoption or drop-out by patients was shown to be an important consideration. 36,37 In some other research, the inherent demands for interactivity were found to be less tolerable for some patients, leading to low completion rates, and some patients were found to drop out before programme completion due to the treatment being so effective in the early stages that further participation was unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a noteworthy finding is that the acceptability of telephone-delivered CBT was worse in our sample of heart transplant recipients compared with other chronic disease populations. For example, the MoodCare study similarly involved a course of telephone-delivered CBT for patients hospitalised with acute coronary syndrome who reported depressive symptoms with a PHQ-9 score more than 5 [22]. Yet in the Mood Care study, 61 % of the 61 participants who were randomised to the intervention group completed five or more CBT sessions and the median number of sessions was eight [22].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the MoodCare study similarly involved a course of telephone-delivered CBT for patients hospitalised with acute coronary syndrome who reported depressive symptoms with a PHQ-9 score more than 5 [22]. Yet in the Mood Care study, 61 % of the 61 participants who were randomised to the intervention group completed five or more CBT sessions and the median number of sessions was eight [22]. It should be noted, though, that 32 % of participants in the Mood Care study who were eligible for inclusion based on initial screening that took place in hospital either withdrew or were lost to follow-up at a second screening undertaken just prior to randomisation [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation